Single-cell transcriptomics reveals peripheral immune responses in non-segmental vitiligo - Yang, Pengju; Luan, Mei; Li, Weizhe; Niu, Mengtian; He, Qiannan; Zhao, Yixin; Chen, Jianan; Mao, Binyue; Mou, Kuanhou; Li, Pan (Frontiers in Immunology, 2023)
Background: Vitiligo is a common autoimmune depigmented dermatology due to destruction of melanocytes. Much evidence suggests that vitiligo is associated with systemic immune activation. Previous studies have focused on immune cell infiltration in and around lesion areas, but few studies have investigated the cell types and function of circulating immune cells in peripheral blood. Here, single cell RNA-sequencing (scRNA-seq) was used to investigate the mechanisms of peripheral immune responses in vitiligo patients. Methods: Peripheral blood was collected from five patients with progressive non-segmental vitiligo and three healthy controls. Peripheral blood mononuclear cells (PBMCs) were obtained by Ficoll-Paque density gradient centrifugation, and scRNA-seq was performed on isolated cell populations to obtain single cell transcriptomes and characterize important genes and intracellular signaling pathways. The key findings were validated with qPCR and flow cytometry assays.Results: We identified 10 major cell types by scRNA-seq. Among these cell types, neutrophils were specifically observed in our scRNA-seq data from PBMCs. Peripheral blood effector CD8+ T cells from vitiligo patients did not show significant differences at the transcriptome level compared with healthy controls, whereas regulatory T cells showed pro-inflammatory TH1-like properties. Innate immune cells, including natural killer cells and dendritic cells, showed increased antigen processing 2 This is a provisional file, not the final typeset article and presentation as well as upregulated interferon responses. B cells, monocytes, and neutrophils all showed activation. B cells, especially memory B cells, had upregulated expression of genes related to humoral immunity. Monocytes showed production of proinflammatory cytokines and chemokines. Neutrophils showed strong chemokine ligand-receptor (L-R) pair (CXCR8-CXCR2) autocrine signaling pathway.Conclusion: This study revealed the genetic profile and signaling pathway characteristics of peripheral blood immune cells in vitiligo patients, providing new insights into its pathogenesis, which may facilitate identification of potential therapeutic targets.